THE INFLUENCE OF WORD OF MOUTH AND PRODUCT QUALITY ON MEDIATED LOYALTY BY PURCHASING DECISION FURNITURE BY CONSUMERS - Juwariyah, Nurul; Hasanah, Nur; Akriana, Fajar; Santoso, Aprih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
The purpose of this research is to analyze the influence of product quality, price perception and location on customer satisfaction at Warmindo Barokah Kedungmundu. The population in this study were Warmindo Barokah Kedungmundu customers. The research method used was purposive sampling. The data used were 99 respondents using the questionnaire data collection method. Data analysis uses multiple linear analysis. The results from respondent data prove that product quality has a positive and significant effect on customer satisfaction. Price perception has no effect on customer satisfaction and location has a positive and significant effect on customer satisfaction.